Eddie Rickenbacker papers - Rickenbacker, Eddie, 1890-1973.; Rickenbacker, Eddie, 1890-1973.
Correspondence, speeches, writings, notes, newspaper clippings, printed matter, and other papers concerning Rickenbacker's career as an aviator and U.S. Army officer in World War I, chairman of the board of Eastern Air Lines, inc., and advocate of conservative causes. Documents his activities with the America First Committee, Committee for the Monroe Doctrine, Committee of One Million Against the Admission of Communist China to the United Nations, Conservative Party of New York State, the John Birch Society, and the radio program, Manion Forum. Includes drafts of his autobiography, Rickenbacker (1967).
Library of Congress Motion Picture, Broadcasting and Sound Division.
Army officer and aviator. Full name: Edward Vernon Rickenbacker.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: America First Committee; Committee for the Monroe Doctrine; Committee of One Million Against the Admission of Communist China to the United Nations; Conservative Party of New York State; Eastern Air Lines, inc; John Birch Society; Manion forum (Radio program); Aeronautics; Aeronautics, Commercial -- United States; Conservatism -- United States; World War, 1914-1918 -- Aerial operations, American; United States -- Politics and government -- 20th century; Army officers; Aviators